Entrepreneurs’ motivation and satisfaction towards online video-based training and advertisement / Mariani Mohd Dahlan - Mohd Dahlan, Mariani (2022)
This study arose from the researcher's concern and investigation of the inadequacies of Bumiputera SME entrepreneurs in marketing and network business. The goal of this study was to investigate entrepreneurs' motivation and satisfaction with online video-based training. The participants were selected from the new MARA Small Medium Enterprises (SMEs) in Perak, Malaysia and the research method used was a mixed-method sequential explanatory design that included both quantitative and qualitative methods. The independent variables were video-based Facebook training (vFB-Ads) and FB Advertisement (FB Ads). The entrepreneurs' perceived motivation and satisfaction were the dependent variables. A total of 31 entrepreneurs were chosen at random from MARA Negeri Perak. The collected data were analysed using descriptive and inferential statistics. The analysis of the entrepreneurs' perceived motivation towards vFB-Ads revealed that the vFB-Ads drew their attention and were relevant to them. The entrepreneurs' trust and satisfaction with vFB-Ads were also high. Meanwhile, the findings showed that entrepreneurs were pleased with the vFB-Ads and FB Ads.